Current understanding of the pathogenetic relationships between chronic obstructive pulmonary disease and type 2 diabetes mellitus: an integrative review - Sanina , N.A.; Sutyrin, D.O.; Turlyun , T.S. (Medicni Perspektivi, 2025)
Currently, chronic obstructive pulmonary disease (COPD) is considered a systemic disease with multiple extrapulmonary effects, which is caused by systemic manifestations of the inflammatory process. On the other hand, obesity, oxidative stress, chronic hyperglycemia, and insulin resistance, inherent in type 2 diabetes mellitus (DM), are key factors for enhancing the body's inflammatory response. Our study aimed to review the existing scientific literature to determine the patterns, relationships, and pathogenetic relationships between type 2 diabetes mellitus and chronic obstructive pulmonary disease. The empirical research method of modern English-language medical literature was used in depth from 2003 to 2024, using search engines on the PubMed and Google Scholar platforms and the Scopus and Web of Science abstract scientific literature databases, and the Cochrane scientific library. Based on the search results, 59 information sources were selected and processed.The analysis used system-structural, formal-logical, bibliographic, and informal (traditional) methods. The authors designed their own figures to visually present information using the infographic methods based on the Miro web resource (miro.com). It has been shown that patients with type 2 diabetes mellitus have an increased risk of developing COPD due to active systemic inflammation, obesity, insulin resistance, and oxidative stress. In addition, hyperglycemia contributes to decreased lung functional parameters and airway remodeling. Adipose tissue plays a vital role in the pathogenesis of COPD and type 2 diabetes mellitus by producing adipokines, such as leptin, resistin, adiponectin, and omentin. An imbalance between pro- and anti-inflammatory adipokines contributes to chronic inflammation, leading to lung function deterioration. Oxidative stress caused by chronic hyperglycemia is an essential factor in the pathogenesis of COPD. Reactive oxygen species (ROS) activate signaling pathways that lead to chronic inflammation and damage to lung tissue. Chronic hyperglycemia affects the function of bronchial smooth muscles, causing its hyperreactivity and excessive proliferation, which can worsen the course of COPD. Thus, COPD and type 2 diabetes are closely interconnected at the level of pathogenetic mechanisms, and the presence of one of these diseases may contribute to the development and progression of the other. Further studies of these relationships may contribute to developing more effective approaches to diagnosing, treating, and prevention of given pathologies.